Providing childcare - HO, Christine (Institutional Knowledge at Singapore Management University, 2021)
Women’s economic empowerment has been hailed as one of the most remarkable revolutions in the past 50 years. Yet, women still face the lion’s share of the burden of childcare despite major progress in their education and earnings capacity. This is particularly salient in many Asian countries. This chapter proposes a synthesis of the state of knowledge on childcare and discusses policy-relevant issues applicable to the Singapore context. Selected policies are documented and lessons from the international landscape are discussed. Raising children incurs both direct costs in the form of childcare and opportunity costs in the form of career costs. This chapter first discusses the trade-offs between childcare, maternal employment, and fertility. Common forms of childcare support available to parents with young children are then documented. These include baby bonus, parental leave, formal childcare subsidies, and grandparents’ help. The efficacy of such support is discussed with regard to fertility and labour supply. Finally, some future directions for childcare policy research are suggested; in particular, flexible parental leave policies that enable mothers and fathers to more efficiently share parental leave, as well as formal childcare subsidies coupled with good quality childcare.